Dampak Abrasi Terhadap Kondisi Sosial Ekonomi Masyarakat Kecamatan Kedung, Jepara - Desy Ismiyanti; Imam Buchori (Jurnal Pembangunan Wilayah dan Kota, 2021)
All the time the coastline has always changes, the change is abrasion or accretion. Changes in the coastline not only have an impact on physical conditions but also affect the socio-economic conditions of the community. This study aims to determine the impact of abrasion on the socio-economic conditions of the community in Kedung District, Jepara. The method used is the descriptive quantitative, a combination of LVI (Livelihood Vulnerability Index) and LVI-IPCC (Livelihood Vulnerability Index - Intergovernmental Panel of Climate Change).  The data used is the result of questionnaires distributed to household. The results of this study indicate that the most influential social impact is the emergence of anxiety and can affect social conditions between communities. While the impact on the economy can be seen in the value of LVI 0.28 which means it is quite vulnerable, and the value of LVI-IPCC 0.037 which means quite vulnerable.  Many of community who choose to have side jobs to fulfill their daily needs, even changing their livelihoods from the coastal sector to non-coastal sectors such as trading, labor, and etc.